2009
DOI: 10.1089/gtmb.2008.0094
|View full text |Cite
|
Sign up to set email alerts
|

Detection of MEFV Gene Mutations in Patients with Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) with ulcerative colitis (UC) and Crohn's disease (CD) as the most common forms is an inflammation of the gastrointestinal tract. Familial Mediterranean fever (FMF) is another inflammatory disease as well. In the current study we studied FMF gene mutations in 47 patients with IBD and 25 healthy individuals to investigate the effects of these mutations on the clinical status of IBD. Twelve mutations were analyzed by reverse hybridization after multiplex PCR amplification of DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
0
17
3
Order By: Relevance
“…Other inflammatory diseases including IBD accompany FMF with a gradually increasing frequency. In addition, the frequency of other inflammatory diseases (including juvenile rheumatoid arthritis) increases in conditions where IBD accompanies FMF (10)(11)(12). The fact that MEFV gene mutations are found with an increasing frequency in these inflammatory diseases supports this (13).…”
Section: Introductionmentioning
confidence: 88%
“…Other inflammatory diseases including IBD accompany FMF with a gradually increasing frequency. In addition, the frequency of other inflammatory diseases (including juvenile rheumatoid arthritis) increases in conditions where IBD accompanies FMF (10)(11)(12). The fact that MEFV gene mutations are found with an increasing frequency in these inflammatory diseases supports this (13).…”
Section: Introductionmentioning
confidence: 88%
“…109 However, some studies have found an increased frequency of MEFV mutations in persons with UC, especially those with episodic arthritis, and this may suggest a possible modifying effect of MEFV in the disease process. 21,110,111 Other studies have found that CD seems to be more prevalent in FMF and presents later than in patients without FMF. 112,113 FMF in this group of patients shows a higher attack frequency and is more often complicated by amyloidosis.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…In Turkey, the estimated prevalence is 1/1,000 and the carrier rate is 1/5 [9,10]. An increased prevalence of some other inflammatory diseases with FMF has been reported, including IBD [11][12][13][14][15][16][17][18]. The gene responsible for FMF, MEFV, is located on chromosome 16p13 and encodes pyrin protein, which is believed to be associated with interleukin-1 (IL-1) and NFjB-related inflammation [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The studies about concordance of IBD and FMF suggested that there is a relation between IBD and FMF, and MEFV mutation has a disease-modifying effect on IBD [11][12][13][14][15][16][17][18]. IBD and FMF share some common clinical features such as abdominal pain, diarrhea, arthralgia, arthritis, and fever.…”
Section: Introductionmentioning
confidence: 99%